Genealogi Kritik Hermeneutik Sunni terhadap Sekte Syiah: Analisis Pemikiran Abdul Halim Mahmud - Nuraini; Muhajirin (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This article investigates the genealogical roots of Sunni hermeneutic criticism directed at the esoteric exegesis (tafsir batiniyah) practiced by Shia sects, as articulated by Shaykh Abdul Halim Mahmud, the Grand Shaykh of Al-Azhar. Through a qualitative literature review, this study analyzes Mahmud’s critique of Shia interpretive authority rooted in the concept of infallible Imams and inner meanings of the Qur’an. Mahmud’s stance differentiates between extreme and moderate Shia groups, emphasizing epistemological divergence in their approach to scripture. Rather than adopting a polemical tone, Mahmud applies a systematic theological evaluation that aligns with Sunni hermeneutic principles. His position contributes to a more nuanced understanding of intra-Islamic discourse by rejecting blanket takfir while preserving doctrinal boundaries. This study finds that Mahmud’s critical approach not only offers a model of balanced inter-sectarian engagement but also reinforces the importance of textual integrity and rational interpretation in Qur’anic scholarship.